Legal Analysis of the Authority of the Ombudsman of the Republic of Indonesia of Riau Province in Encouraging Compliance With the Implementation of Decisions of The Pekanbaru State Administrative Court Which Are Not Implemented by State Administrative - Fahrur Rozi; Dodi Haryono; Separen Separen (Peneliti.net, 2026)
The principle of Indonesia as a state based on the rule of law (Rechtsstaat) guarantees citizen protection through the Administrative Court (PTUN) mechanism. However, the effectiveness of PTUN decisions is frequently hindered by the low compliance of Administrative Officials in executing final and binding decisions (inkracht van gewijsde), including in Riau Province. This phenomenon of non-compliance constitutes a form of maladministration that threatens legal certainty. This research employs a socio-legal method, combining normative approaches with the analysis of legal implementation in the field within Riau Province for the 2020–2024 period. The results indicate that although the Ombudsman possesses the authority to supervise the neglect of legal obligations (undue delay), its effectiveness in Riau remains limited. Data from 2020–2024 reveals that only a small portion of reports regarding PTUN decision execution were successfully resolved to the closed-report stage. The main obstacles include low legal awareness among public officials, perceptions of weak binding force of recommendations, and limitations of authority that cannot intervene in judicial technical matters. Optimizing this role requires strengthening administrative sanctions against defiant agencies and enhancing inter-institutional coordination to ensure the coercive power of PTUN decisions in achieving good governance.